P213 Frontal eye fields control visual cortex excitability by phase aligning beta oscillations: A bifocal transcranial magnetic stimulation (TMS) study. Issue 3 (March 2017) - Veniero, D.; Morand, S.; Duecker, F.; Sack, A.T.; Gross, J.; Thut, G.
Abstract : Question: Previous TMS studies have shown that attention-regulated changes in posterior brain rhythms are under FEF control (Capotosto, JNeurosci 2009) and that FEF-TMS affects the probability of perceiving phosphenes (Silvanto, JNeurophysiol 2006). However the oscillatory nature of the latter changes has never been examined. Here we specifically tested whether FEF-TMS causes visual cortex excitability to phase align at the frequency of brain rhythms. Methods: To this end we used bifocal TMS. The first pulse was used to activate FEF projections to visual areas, the second pulse to test the resulting excitability changes in primary visual cortex (V1) or extrastriate cortex (V5) in terms of phosphenes perception as a function of the interval between pulses. If FEF activation phase-aligns oscillatory activity over the occipital cortex, one would expect a periodicity in phosphenes perception locked to the FEF-TMS pulse. Thirteen participants were enrolled to assess right FEF-right V1 (rFEF-rV1) or rFEF-rV5 interactions at 19 time delays (30 to 300 ms). The specificity of FEF-V1/V5 interactions was controlled for by means of two control conditions (Cz-rV1, Cz-rV5). To test for a cyclical pattern in phosphene perception, we fitted cosine waves between 7 and 25 Hz, extracted the R-squared values for each frequency and statistically evaluated the difference between each main condition and its control (FEF-V5 vs Cz-V5; FEF-V1 vs Cz-V5) using a bootstrapping procedure. Results: When comparing rFEF-rV5 and Cz-rV5, we found beta-frequency (from 14 to 19 Hz) to better fit the rFEF-rV5 than its control condition. Notably, when testing for phase locking, we found significant results in the beta band (16–17 Hz) for the rFEF-rV5 condition. When comparing rFEF-rV1 and Cz-rV1 we found no significant difference in the R-squared values at any frequency. Conclusions: Our data are in line with FEFs controlling V5 excitability by phase resetting oscillatory activity in the beta band, which accords with findings suggesting that beta oscillations are involved in top-down interactions within cortical networks (Buschman, Science 2007).